Studi Komparatif Analisis Struktur Portal 3D Dan Rangka Batang 3D Menggunakan Metode Elemen Hingga dan SAP2000 - Islami, Dian Nanda; Fan Putra, Muhammad Rifal (Dept. of Civil Engineering Universitas Riau, 2025)
The comparative accuracy of different structural models under Finite Element Method (FEM) computation remains a relevant issue, particularly when manual, spreadsheet-based formulations are compared with professional engineering software. This article integrates the findings of both studies as a basis for comparative analysis, namely (1) 3D portal analysis using MS Excel-based FEM validated with SAP2000, and (2) 3D truss analysis using a similar approach. This study aims to assess the consistency of manual analysis results based on Excel with the numerical results of modern software, as well as to understand the advantages and limitations of the method in the context of different structures. The results of the study show that in 3D portals, the displacement difference is relatively small (<5%), but the internal moment force shows a significant difference. Conversely, in 3D truss structures, axial forces and support reactions were almost identical to SAP2000, while displacement had a considerable deviation (±10%). This confirms that Excel-based MEH is effective as a simple educational and verification tool, but in professional practice, analysis software is still needed to ensure accuracy, especially for internal force analysis in 3D portals.